Sliding-Mode Formation Control for Cooperative Autonomous Mobile Robots - Defoort, M.; Floquet, T.; Kokosy, A.; Perruquetti, W. (IEEE transactions on industrial electronics (1982), 2008)
This paper considers the control of a group of autonomous mobile robots. A coordinated control scheme based on a leader-follower approach is developed to achieve formation maneuvers. First and second order sliding-mode controllers are proposed for asymptotically stabilizing the vehicles to a time-varying desired formation. The latter controller, based on the relative motion states, eliminates the need for measurement or estimation of the leader velocity. It enables formation stabilization using a vision system carried by the followers and ensures the collision avoidance from the initial time instance. Experimental investigation has been conducted using a test bench made of three nonholonomic mobile robots in order to demonstrate the effectiveness of the proposed strategy.